Electrochemical Sensing of Serotonin in Food Products by Electrochemically Fabricated S-Doped Graphene Oxide Electrode - Serbest, Zeynep; Gorduk, Ozge; Sahin, Yucel (PLEIADES PUBLISHING LTD, 2023)
The aim of this study is to develop an electroanalytical method for the determination of serotonin, a very important neurotransmitter for neuroscience in food products, with an electrochemically produced sulfur-doped graphene oxide modified pencil graphite electrode (EGO/PGE). The S-doped graphene oxide electrode was fabricated by chronoamperometry, a fast, environmentally friendly, and, more importantly, functional group doping technique in one step. Techniques such as atomic force microscopy, electrochemical impedance spectroscopy, cyclic voltammetry, energy-dispersive X-ray spectroscopy, scanning electron microscopy, and Fourier-transform infrared spectroscopy were used for the structural and morphological characterization of the produced sensor. The limit of detection and limit of quantitation were calculated as 0.026 and 0.09 mu M, respectively, using differential pulse voltammetry under optimum experimental conditions with the prepared EGO/PGE. Recovery tests were performed by spiking different concentrations into walnut and milk samples to investigate the applicability of the developed method in food samples. Good results between 93.1 and 105.8% were obtained in recovery studies. These results showed that the developed S-doped graphene oxide modified pencil graphite electrode platform was practically applicable in food samples due to its simplicity, low cost, fast response time, easy manufacturing, good selectivity, and high sensitivity.
Keywords: neuroscience; serotonin; graphene oxide; cyclic voltammetry; differential pulse voltammetry; DOPAMINE; SENSOR; Chemistry